2010
DOI: 10.1074/jbc.m109.049700
|View full text |Cite
|
Sign up to set email alerts
|

GABAB Receptor Constituents Revealed by Tandem Affinity Purification from Transgenic Mice

Abstract: GABA B receptors function as heterodimeric G-protein-coupled receptors for the neurotransmitter ␥-aminobutyric acid (GABA). Receptor subtypes, based on isoforms of the ligandbinding subunit GABA B1 , are thought to involve a differential set of associated proteins. Here, we describe two mouse lines that allow a straightforward biochemical isolation of GABA B receptors. The transgenic mice express GABA B1 isoforms that contain sequences for a two-step affinity purification, in addition to their endogenous subun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 56 publications
1
44
0
Order By: Relevance
“…Association of auxiliary KCTD8, -12, -12b, and -16 subunits with principal GABA B receptor subunits was recently shown to generate molecularly and functionally distinct receptor subtypes (5,6,9,28). The four KCTD proteins are built from obligatory T1 and H1 domains and optional H2 domains.…”
Section: Discussionmentioning
confidence: 99%
“…Association of auxiliary KCTD8, -12, -12b, and -16 subunits with principal GABA B receptor subunits was recently shown to generate molecularly and functionally distinct receptor subtypes (5,6,9,28). The four KCTD proteins are built from obligatory T1 and H1 domains and optional H2 domains.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, stringent purification procedures, such as tandem affinity purification (TAP), reduce nonspecific binding but could lead to loss of transient interactions. Most published studies did not employ quantification, which makes it difficult to distinguish genuine interaction partners from nonspecific contaminants (15)(16)(17)(18). Quantitative affinity purification and mass spectrometry solves this problem by using quantification as an additional filter (19 -21).…”
mentioning
confidence: 99%
“…However, the authors recommended starting with 3 9 10 7 cells for standard purification of protein complexes using the proposed procedure. Recently, using this SBP-HA tag and following a similar protocol, Bartoi et al (2010) and Wyler et al (2011) successfully isolated GABA B receptor complexes from transgenic mice and ribosomal subunit precursors from HEK 293 cells, respectively. Li et al (2011) reported the efficient purification of protein complexes from mammalian cells using a SBP-His tandem tag.…”
Section: Sbp-hamentioning
confidence: 98%